Differentiation and Intimate Partner Violence. Issue 5 (20th October 2017) - Likcani, Adriatik; Stith, Sandra; Spencer, Chelsea; Webb, Farrell; Peterson, Frank Ryan
ABSTRACT: This study explored the impact of differentiation of self on Intimate Partner Violence (IPV). We sought to determine if an individual's level of differentiation of self in a relationship adds to the variance accounted for in IPV perpetration by known risk factors, i.e., relational satisfaction, marital conflict, romantic jealousy, depression, and anxiety . Results indicated that differentiation of self in a relationship is a predictor for perpetration of physical intimate partner violence even after controlling for other known risk factors.